2021
DOI: 10.1111/1365-2745.13719
|View full text |Cite
|
Sign up to set email alerts
|

Variation in resource allocation strategies and environmental driving factors for different life‐forms of aquatic plants in cold temperate zones

Abstract: 1. Resource allocation, including biomass allocation and nutrient allocation between different organs in a plant, reflects the trade-off in partitioning between aboveground and below-ground organs and the growth and adaptation strategies of plants in a changing environment. Although varied resource allocation patterns among different organs in different functional groups of terrestrial plants have been found, few studies have focused on freshwater ecosystems.2. In this study, to clarify biomass and nutrient al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 95 publications
1
6
0
Order By: Relevance
“…However, as the petiole vascular area in aquatic plants and stem xylem area in terrestrial woody plants are not anatomically identical, we need to investigate additional lineages, such as terrestrial herbaceous plants, with similar vascular bundle structures in the stems to clarify the mechanisms of such similar scaling patterns. The origin of allometric scaling in plants and animals has been debated heatedly ( Beuchat, 1997 ; West et al , 1997 ; Hu et al , 2021 ; Koyama and Smith, 2022 ; Santoro and Calzada, 2022 ), and our study can act as a case study to show various trait coordination in leaf and petiole (or stem) between aquatic and terrestrial plants.…”
Section: Discussionmentioning
confidence: 94%
“…However, as the petiole vascular area in aquatic plants and stem xylem area in terrestrial woody plants are not anatomically identical, we need to investigate additional lineages, such as terrestrial herbaceous plants, with similar vascular bundle structures in the stems to clarify the mechanisms of such similar scaling patterns. The origin of allometric scaling in plants and animals has been debated heatedly ( Beuchat, 1997 ; West et al , 1997 ; Hu et al , 2021 ; Koyama and Smith, 2022 ; Santoro and Calzada, 2022 ), and our study can act as a case study to show various trait coordination in leaf and petiole (or stem) between aquatic and terrestrial plants.…”
Section: Discussionmentioning
confidence: 94%
“…Furthermore, as the most direct source of plant growth and nutrients, soil properties are largely responsible for elemental concentrations and stoichiometric ratios in plants growing in riparian zones ( Ding et al., 2022 ). From an ecological and evolutionary standpoint, the distinct ecological niches occupied by plants of different life types contribute to variations in their nutrient demands and utilization strategies, providing a more direct reflection of nutrient allocation and utilization strategies ( Tian et al., 2018 ; Hu et al., 2021 ; Xiong et al., 2021 ). Recent studies further indicate that riparian plants in the TGRR develop species-specific traits and functional groups following prolonged inundation ( Su et al., 2020 ; Zhang and Xie, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have indicated that organs such as roots can more accurately determine plant nutrient limitation traits than leaves ( Tian et al., 2018 ; Yin et al., 2021 ). Nutrient partitioning among different plant organs reflects their trade-offs in accessing aboveground and belowground resources ( Hu et al., 2021 ). Riparian plants must effectively allocate limited resources among organs to withstand the combined stresses of inundation and nutrient limitation ( Jing et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Partial least squares path models (PLS-PMs) were constructed to test the direct and indirect effects of water properties (T, DO, Cond, pH and Turb), water nutrients (TN, TP, COD, NO 3 -N and NH 3 -N) macrophyte traits (MB and MC) and allelochemicals (alkaloids, amines, esters, organic acids and phenols) on epiphytic algal abundance (Table S5) (Hu et al, 2021). Linear regressions were used to test the patterns of epiphytic algal abundance along the biomass and coverage gradients of the three macrophytes in the field investigation and mesocosm experiment.…”
Section: Discussionmentioning
confidence: 99%